A Scoping Review of Gender Differences in Suicide in India - Ramesh, Parvathy; Taylor, Peter J.; McPhillips, Rebecca; Raman, Rajesh; Robinson, Catherine (Frontiers in Psychiatry, 2022)
Introduction Much of the published literature on suicide comes from high income countries. In countries such as India, female suicide rates exceed the global suicide rate and suicide rates found in their male counterparts. Results from previous studies indicate that factors related to suicide among men and women in India are different from those seen in high-income countries. To date, no reviews have considered the relationship between gender and suicide in India. Therefore, the aim of this scoping review is to provide a comprehensive understanding of existing literature reporting gender differences in suicide rates, methods, risk factors and antecedent factors in India by reviewing published studies. Method A scoping review was conducted to map the existing literature on gender differences in suicide in India. To identify peer-reviewed publications, online databases PsycINFO and Embase were searched. The search terms were [suicid* AND India*]. The searches took place in November 2020 and May 2021, with no language restrictions. Articles published from 2014 onwards from India were included. Reference lists of selected studies were searched for studies that could meet the inclusion criteria. Results This review identified 17 studies that met the inclusion criteria. The ratio between women and men who die by suicide in India is much lower than in high-income countries. Hanging was found to be a more commonly used method of suicide among both men and women, in comparison to high-income countries where hanging is more common among men. This review also identified several gaps in the literature. There were few studies that examined suicide among transgender Indians. There was limited literature on gender differences in risk and protective factors for suicide. Limitations such as the omission of a lack of gender-based analyses in several studies and under-reporting of suicide rates were identified. Conclusion Understanding suicide within the context of individual countries is essential in designing culture-appropriate suicide prevention strategies. This review identified an urgent need to establish and evaluate suicide surveillance systems in India. Furthermore, additional research is warranted to understand suicide among individuals who identify outside the gender binary, and gender-specific risk and protective factors.